Metropolitan governance and infrastructure in São Paulo: the challenge of mediating regional interests and local impact - Marcelo Sacenco Asquino (Pós: Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2010)
The formation of the São Paulo metropolis is related to the historical process of building regional infrastructure as of the late 19th century, in connection with economic motivation and territorial influences. Since that time, São Paulo has played a key role in the network of cities that has been fundamental to its economic development and to its recognition as the most important city in Brazil. This article examines the importance of understanding the regional scale in relation to São Paulo's plans and projects, from Plano de Avenidas (Avenue Plan) in the 1930s to the Rodoanel (ring road) in the 1990s; the experience of planning and management of the metropolitan system in the 1970s and, in contrast, the environmental licensing process of these large projects after the 1990s. Discussing São Paulo's plans and projects is a complex task, because a project's local impact as well as regional interests must be considered. From different perspectives, the author reviewed the results of environmental licensing of Ampliação da Calha do Rio Tietê (deepening the bed of the Tietê river) and Rodoanel Trecho Sul (south section of the ring road) projects, and their actual role in the future arrangement and development of the São Paulo metropolis. Based on (a) the results of the metropolitan planning experience in the 1970s, (b) the updating of the metropolitan discussion in the 1990s from an economic globalization perspective, and (c) the current experience of metropolitan systems in the state of São Paulo, it seems necessary to re-establish an effective metropolitan planning and management system in order to guarantee its legitimacy, commitment and governance.